IMPLEMENTASI KOMUNIKASI PEMASARAN BERBASIS SOCIAL MEDIA MARKETING PADA INSTAGRAM WISATA SESAOT - Ni Luh Sueni Widyanti; Erri Supriyadi; Muhammad Azizurrohman (Journal Of Responsible Tourism, 2022)
The development of increasingly advanced and modern information dissemination also has an impact on the field of tourism marketing, one of which is for tourism village marketing communications. Sesaot Village is a village that has a fairly rapid development of tourism activities and has a variety of tourism potentials that can be used as supporting attractions. This village also utilizes the use of Instagram as a marketing communication medium. However, the use of Instagram as a marketing communication medium has not been maximized and the use of tourism potential as marketing communication content is minimal. Thus, this study aims to determine the application of Instagram-based marketing communications and to describe the use of tourism potentials in wisata PUREKMAS so that it can be used as marketing communication content on Instagram wisata sesaot. This study uses in-depth interviews, non-participant observation, and documentation and uses a qualitative descriptive approach. The results of the study indicate that there are obstacles in the application of marketing communications on Instagram wisata sesaot, such as constraints on human resource managers, packaging of content that is less attractive, and the application of components on marketing communication indicators that are not optimal.